2012
DOI: 10.5507/bp.2012.037
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypoglycaemia requiring the assistance of emergency medical services - frequency, causes and symptoms

Abstract: Aims.To evaluate the incidence of severe hypoglycaemia (SH) requiring the assistance of Emergency Medical Services (EMS) in the general population of the Hradec Králové region, in a 1 year period; to describe the distribution of these events throughout the day, and to analyse the symptoms and causes. Methods. The outcome data were obtained from special forms which were filled in by EMS medical staff. Incidence of SH was calculated and the distribution of events throughout the day was analysed using contingency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
6
1
2
Order By: Relevance
“…Pareto analysis for population FRIDs was applied using the ATC codes recursively up to the second level; at each level, the frequency had to achieve at least 60% of drugs to proceed the next Pareto analysis of the lower ATC level. Multivariate analysis, specifically the tree-based technique (Krnacova et al, 2012), was performed to analyse dependencies of the metric variables (differences in the physicians' and pharmacists' opinions) on a larger number of non-independent binary variables (presence of FRIDs). P-value < 0.05 was considered as statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Pareto analysis for population FRIDs was applied using the ATC codes recursively up to the second level; at each level, the frequency had to achieve at least 60% of drugs to proceed the next Pareto analysis of the lower ATC level. Multivariate analysis, specifically the tree-based technique (Krnacova et al, 2012), was performed to analyse dependencies of the metric variables (differences in the physicians' and pharmacists' opinions) on a larger number of non-independent binary variables (presence of FRIDs). P-value < 0.05 was considered as statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of treatment regimens with insulin, associated with the need for greater attention to glycemic control, may explain the higher incidence of hypoglycemic events in patients under this type of treatment 22 , 33 . The use of simpler regimens and insulin analogs can minimize these risks 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Krnacova et al . [13] study showed that most hypoglycemic episodes were experienced by patients between 2 pm and 6 pm. Another study reported that the lowest glycemia occurred just before the evening meal.…”
Section: Discussionmentioning
confidence: 99%